Endothelial Extracellular Vesicles—Promises and Challenges - Hromada, Carina; Mühleder, Severin; Grillari, Johannes; Redl, Heinz; Holnthoner, Wolfgang (Frontiers in Physiology, 2017)
Extracellular vesicles, including exosomes, microparticles and apoptotic bodies, are phospholipid bilayer-enclosed vesicles that have once been considered as cell debris lacking biological functions. However, they have recently gained immense interest in the scientific community due to their role in intercellular communication, immunity, tissue regeneration as well as in the onset and progression of various pathologic conditions. Extracellular vesicles of endothelial origin have been found to play a versatile role in the human body, since they are on the one hand known to contribute to cardiovascular diseases, but on the other hand have also been reported to promote endothelial cell survival. Hence, endothelial extracellular vesicles hold promising therapeutic potential to be used as a new tool to detect as well as treat a great number of diseases. This calls for clinically approved, standardized, and efficient isolation and characterization protocols to harvest and purify endothelial extracellular vesicles. However, such methods and techniques to fulfill stringent requirements for clinical trials have yet to be developed or are not harmonized internationally. In this review, recent advances and challenges in the field of endothelial extracellular vesicle research are discussed and current problems and limitations regarding isolation and characterization are pointed out.